Development of Animation Based Arabic Online Learning Media for Arabic Language Education Students of UIN K.H. Abdurrahman Wahid Pekalongan - Akhmad Aufa Syukron; Faliqul Isbah; Muhamad Jaeni; Akhmad Zaeni (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
The research aims to develop an effective animation-based Arabic online learning media for Arabic Language Education students, and to determine the level of feasible and valid of the online learning media for Arabic Language Education students of UIN K.H. Abdurrahman Wahid Pekalongan. The research uses the Research and Development (R&D) method with the ADDIE model which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 15 students who were selected through random sampling techniques. Data collection was carried out through interviews, observations, questionnaires, and expert validation. The results of the study showed that the developed media obtained a validation score of 4.68 from media experts and 4.74 from material experts who showed the "Very Feasible" category. The students' response to the media obtained an average score of 4.60 with the category of "Excellent". This study concludes that animation-based online learning media is effective in visualizing abstract Arabic concepts, increasing learning engagement, and can be integrated as an alternative media for Arabic language courses. Recommendations for future research are the development of advanced materials and the adaptation of more interactive platforms.